An Analysis of the World Paper Industry With a Focus on Europe and Trade Perspective - Aytaç , Ayhan; Korkmaz, Murat (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2022)
The pulp and paper manufacturing industry is currently facing sweeping changes due to the fact that supply and demand are dominated by different global players. These changes have significant effects not only on the paper and pulp production of countries but also on world economies thanks to the high level of trade between countries around the world. Based on the historical development of paper, our study examines today's production around the world economies, shows the latest commercial trends in the paper and pulp trade, and makes a prediction on the effects of the data belonging to this sector on the trade of countries through using panel regression models. According to our results, we determined a significant relationship between the total world paper and cardboard production in Turkey and the European Union and the amount of pulp. On the other hand, a partial relationship was found between the European Union and Turkey's paper production. In addition, we concluded that the amount of pulp used in paper and cardboard production was the factor causing the total paper production in the European Union and Turkey. In other words, we have established as a result of the analysis that as the amount of pulp used in paper and cardboard production increases, paper and cardboard production also increases at the same rate.